Evaluation of fungicide, fertilizer, and plant growth regulator treatments for management of pink and gray snow mold on golf course turfgrass in New Hampshire 2023-2024 - Soonhong Min; Jaime C. Piñero (Plant Health Progress, 2026)
Pink snow mold and grey snow mold, caused by Microdochium nivale and Typhula incarnata, are significant turfgrass diseases that occur under prolonged snow cover and cool wet conditions. Pink snow mold is identified by small water-soaked spots that turn reddish-brown before fading to tan, often with a pink mycelial margin. Grey snow mold appears as large matted patches of grey or straw-colored turf after snowmelt. The two diseases differ in appearance: pink snow mold has pink-colored mycelium and sporodochia, while grey snow mold has dense grey mycelium and hard sclerotia. This report evaluates various chemical treatments for controlling both diseases on a Agrostis stolonifera (creeping bentgrass) and Poa annua (annual bluegrass) mixed stand during the 2023-2024 season in New Hampshire. The study assessed disease severity and turf quality, providing valuable insights to golf course superintendents for selecting effective treatments.